Return of State Financial Losses Resulting From Corruption and Money Laundering Crimes - Rosalia Dika Agustanti; Bambang Waluyo; Amanda Putri Kurniawan (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2023)
Corruption has become a rampant habit within society. Corruption is a manifestation of greed in people, which they will never feel enough of the wealth they already have. One form of criminal act other than corruption that is common in Indonesian society is the Money Laundering Crime. In this journal, we examine the legal liability and principle of returning state financial losses and the application of asset forfeiture in efforts to return state finances. Under the money laundering law, judges are given the authority to be able to confiscate and expropriate the property of defendants who commit crimes of corruption and money laundering even before the fall of the judge's ruling in court. The recovery of state assets is a concept that is equal with the concept of restorative justice. The deprivation of assets in the recovery of state financial losses is quite important to quell crime with economic motives. This is because so complex are the acts of economic-motivated lending that they are often difficult and complicated for law enforcement to handle.